New Model Foot and Ankle Service Pathway: Pilot Results 2 Years - Andrea Pujol Nicolas LMS, MRCS (Ed); Jayasree Ramas Ramaskandhan MPT, MSc; Malik Siddique DO (Foot & Ankle Orthopaedics, 2019)
Category: Service improvement Introduction/Purpose: The foot and ankle services at NUTH incorporates both elective and trauma services. The elective service carries out on average 10,500- 11,000 review appointments/ year and 4000-4500 new patient appointments/year. The waiting times for new out-patient appointments were 8-14 weeks. A new pathway was designed with the aim to improve 18 week national target compliance, improve departmental efficiency, and improve patient satisfaction. Methods: A new initial assessment clinic pathways was designed were all new patients are seen in a one hour slot one stop clinic by a dedicated Extended Scope Practitioner. History and clinical examination are taken as well as initial Proms questionnaire, x-ray assessment followed by gate analysis including pain map, treadmill assessment and plantar pressure analysis. A consultant led MDT review of the finding is performed the same week where plan for treatment or further investigations is formulated. Results: A total of 1792 patients had the initial assessment through the new clinic pathway between March 2016 and March 2018. The average waiting time for the initial assessment has been gradually reduced from 14 to 3 weeks. We obtained over 96% patient satisfaction in enhancing patient experience. Conclusion: Our new clinic model has shown to improve efficiency, patient satisfaction and reduce waiting times.